The urgency of anti-corruption education as a local subject in secondary education in Lampung Province - Aida Ratna Zulaiha; Dinn Wahyudin (Inovasi Kurikulum, 2024)
Anti-corruption education is a mandatory local content subject in formal secondary schools in Lampung Province based on the Governor's Regulation. Implementing anti-corruption subjects is carried out by strengthening anti-corruption behavior through a cycle of knowledge, skills, and attitudes to form an anti-corruption attitude in each individual based on their understanding and awareness. This study aimed to determine the implementation process and output of anti-corruption education in senior high schools and vocational high schools in Lampung and to analyze the urgency of anti-corruption education as a local content subject in relation to the objectives of anti-corruption education that have been set. The method used is a combination of analysis of legal documents, modules, and strategies related to anti-corruption education, followed by a survey conducted on schools implementing the program. In most senior high schools and vocational high schools in Lampung that have implemented anti-corruption education as a local content subject, the most dominant aspects taught are attitudes and knowledge, but less for the skills aspect. Based on the objectives of the anti-corruption education set, implementing anti-corruption education only in the form of anti-corruption subjects in local content is not enough. The effectiveness of anti-corruption education in educational units will be achieved if anti-corruption education is implemented comprehensively through curriculum implementation, a conducive ecosystem that supports the internalization of anti-corruption values, and the governance of secondary education units with integrity.   Abstrak Pendidikan Antikorupsi merupakan mata pelajaran muatan lokal wajib pada sekolah menengah formal di Provinsi Lampung yang didasarkan pada Peraturan Gubernur. Implementasi mata pelajaran antikorupsi dilakukan dalam bentuk penguatan perilaku antikorupsi, melalui siklus pengetahuan, keterampilan dan sikap, dengan tujuan terbentuknya sikap antikorupsi pada setiap individu yang didasarkan pada pemahaman dan kesadaran yang dimiliki. Tujuan dari penelitian untuk mengetahui proses implementasi dan output dari pendidikan antikorupsi di SMA dan SMK di Lampung serta menganalisis urgensi pendidikan antikorupsi sebagai mata pelajaran muatan lokal dikaitkan dengan tujuan pendidikan antikorupsi yang ditetapkan. Metode yang dilakukan merupakan kombinasi antara analisis terhadap dokumen hukum, modul dan strategi terkait pendidikan antikorupsi dengan survei yang dilakukan terhadap sekolah pelaksana program. Mayoritas SMA dan SMK di Lampung yang sudah mengimplementasikan pendidikan antikorupsi sebagai mata pelajaran muatan lokal, aspek yang paling dominan diajarkan adalah sikap dan pengetahuan, namun kurang untuk aspek keterampilan. Berdasarkan tujuan dari pendidikan antikorupsi yang ditetapkan, mengimplementasikan pendidikan antikorupsi hanya dalam bentuk mata pelajaran antikorupsi pada muatan lokal tidak cukup. Efektivitas pendidikan antikorupsi di satuan pendidikan akan tercapai jika pendidikan antikorupsi dilaksanakan secara komprehensif melalui implementasi kurikulum, ekosistem kondusif yang mendukung internalisasi nilai antikorupsi, serta tatakelola satuan pendidikan menengah yang berintegritas. Kata Kunci: muatan lokal; pendidikan antikorupsi; peserta didik; sekolah menengah